Peningkatan Kompetensi Guru dalam Menyusun dan Melaksanakan Perangkat Pembelajaran melalui Pelaksanaan Workshop dan Bimbingan Teknis - Musa Kedi (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is an action research that aims to improve the competence of UPTD SD Negeri 163 Barru teachers in compiling and implementing learning tools through Workshop activities and Technical Guidance. This action research was carried out in the Odd Semester of the 2021/2022 Academic Year. The results obtained after the action was carried out in the form of implementing Workshops and Technical Guidance for teachers, namely in the first cycle, the percentage of completeness of learning tools was 85.47% and the percentage of implementation of learning tools was 88.52%. After improvements were made in cycle II, an increase in the percentage of completeness of learning tools was obtained by 96.58% and the percentage of implementation of learning tools by 96.42%. develop and implement learning tools to increase.